Keterlibatan Klerikus Dalam Politik: Tinjauan Hukum Gereja Dan Kesaksian Hidup San Giovanni Xxiii - Alphonsus Tjatur Raharso (Sekolah Tinggi Widya Sasana, 2023)
This research raises the theme of clerical involvement in politics, which still creates pro and con reactions. The questions answered in this research are what, how, and to what extent clerics may engage or are prohibited from engaging in politics. What are the reasons and purposes of the Catholic Church in prohibiting its clergy from engaging in politics? What are the legal consequences for the clerics involved in practical politics? Is there any good example for clerics in engaging in politics? This research uses the normative research method of Church law. The problem is approached using the deductive method, by departing from the legal norms of the Church which are elaborated using documents issued by the Holy See. The research also uses the inductive method through a study on the testimonies of the life of St. John XXIII. The deductive and inductive approaches are combined to find the scope of meaning and the proper and wise application of the ecclesiastical norm regarding clerical involvement in politics. The study found that the clerical mission cannot be separated from politics. The call to configure oneself fully to the person and mission of Christ requires clerics to take the side of the small, the poor, the oppressed, and the marginalized by conducting sharp socio-political criticism agaist unfair, unequal and discriminatory government or economic systems. The teaching of clerics should have a political impact on the lives of the faithful, especially the laity, to the point of encouraging them to become fully involved in practical politics to fight for justice, truth, peace and the common good with other members of society. However, concern for the political problems of the nation must never lead clerics to become directly and actively involved through political parties. Such involvement will divide the communion of the people, will mix politics and religion, and will run the risk of creating hostility both within the Church itself and outside the Church. Violation of the prohibition to actively participate in political parties results in the suspension of the cleric concerned. As the life witnessed by St. John XXIII, clerics are to be fathers of all people, persons of dialogue and peace, above all parties and for all parties. Clerics represent the Church that does not bind itself to any particular political system, and remains present and works in whatever political system, which is democratically selected and established by all citizens